Analyzing the Characteristics of Fuzzy Synthetic Decision Methods on Evaluating Student's Academic Achievement An Empirical Investigation of Junior High School Students in Taiwan - Ching-Sen Hsieh; Chih-Hung Wu; Tao Huang; Yu-Wen Chen (2009 International Conference on Artificial Intelligence and Computational Intelligence, 2009)
Since Taiwan began promoting its educational reforms in earnest in 1998, although the idea of diversity in evaluation is proposed as significant, it overlooks the significance of explaining evaluation results. In terms of the traditional method, it can only use traditional averages and convert them to rankings, but this does not provide further explanatory information, and it is impossible to proceed with more reasonable evaluations, decisions, and interpretations for the learning achievements of students, and provide a fair and appropriate consideration of the evaluation results. Therefore, this study attempts to introduce the fuzzy concept in actual scores and rankings. Using the synthetic decision method of fuzzy theory, the composite operations are used in conjunction with the membership function, and finally fuzzy means are used to express the diverse evaluation results of students. This study hopes to provide grade calculation methods that are suited to students with different characteristics, in order to achieve diverse and precise ranking evaluations. This study uses junior high school first year students in central Taiwan as research subjects, selecting the actual mid-term exam results of the gifted class as research data. The fuzzy synthetic decision method is applied through composite operations, proposing a ranking system that is more diverse and precise than the traditional average method. Results of this study can be used as a reference for educators in the field and future researchers.